2020
DOI: 10.1021/acs.macromol.9b02365
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte Surface Diffusion in a Nanoslit Geometry

Abstract: The surface diffusion of poly-L-lysine (PLL) in a planar nanoslit was studied using convex lens-induced confinement (CLiC) single-molecule tracking microscopy. Three surface chemistries were employed to understand the interplay of electrostatic and short-range interactions: an amine-functionalized silica surface, an oligo(ethylene oxide) (OEG)-modified surface, and a 1:1 mixture of the two ligands. Effective surface diffusion coefficients increased rapidly with slit height until saturating for slit heights <30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 69 publications
(101 reference statements)
2
24
0
Order By: Relevance
“…For example, in analyzing trajectories of negatively charged HSA on charged surfaces, we found that the waiting-time distributions were well-described by power-law functions that broadened as the charge of the surface was made more positive (by deposition of charged organo-silane modifiers), corresponding to a systematic increase in the (negative) power-law exponent. 37,47 This trend reflected increasingly attractive electrostatic interactions. Related phenomena were associated with other types of intermolecular interactions, such as those between dextran and a temperatureresponsive poly(N-isopropylacrylamide) (PNIPAAM) polymer film (Figure 5a), where the dextran exhibited a broad distribution of waiting times at low temperature (where the PNIPAAM film comprised a hydrophilic brush) and a less broad distribution at slightly higher temperatures (where the PNIPAAM collapsed into a dense hydrophobic film), (Figure 5b).…”
Section: A Waiting Timesmentioning
confidence: 96%
“…For example, in analyzing trajectories of negatively charged HSA on charged surfaces, we found that the waiting-time distributions were well-described by power-law functions that broadened as the charge of the surface was made more positive (by deposition of charged organo-silane modifiers), corresponding to a systematic increase in the (negative) power-law exponent. 37,47 This trend reflected increasingly attractive electrostatic interactions. Related phenomena were associated with other types of intermolecular interactions, such as those between dextran and a temperatureresponsive poly(N-isopropylacrylamide) (PNIPAAM) polymer film (Figure 5a), where the dextran exhibited a broad distribution of waiting times at low temperature (where the PNIPAAM film comprised a hydrophilic brush) and a less broad distribution at slightly higher temperatures (where the PNIPAAM collapsed into a dense hydrophobic film), (Figure 5b).…”
Section: A Waiting Timesmentioning
confidence: 96%
“…Lenses and surfaces were prepared via solvent-assisted vapor deposition using a neutral oligoethylene glycol silane, methoxy­(triethyleneoxy)­propyl­trimethoxysilane (Gelest), as previously described to reduce nonspecific adsorption of the DNA samples. In addition, all DNA solutions contained 0.1 mg/mL concentration of BSA (Sigma-Aldrich), which had been previously filtered (Corning), to act as a site-blocking agent.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Single molecule tracking, height profile measurements, and object heights were determined as described previously . The coefficient of variation for confinement heights during a particular trajectory was <10%.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of model was first proposed in the 90's when it was realized that the effective lateral dispersion of molecules adsorbed at a fluid-solid interface is significantly mod-ified by temporary excursions into the fluid [29]. The stochastic motion resulting from interplay of bulk and surface diffusion has recently been directly observed experimentally [30][31][32][33][34]. It is also known that surface mediated transport gives rise to non-trivial effects in the context of target search kinetics [35][36][37][38] and that in certain cases the search efficiency can be tuned via the parameters of the surface mediated diffusion model.…”
mentioning
confidence: 99%